2021
DOI: 10.1055/s-0041-1730891
|View full text |Cite
|
Sign up to set email alerts
|

Pathophysiology of Bronchiectasis

Abstract: Bronchiectasis is a complex, heterogeneous disorder defined by both a radiological abnormality of permanent bronchial dilatation and a clinical syndrome. There are multiple underlying causes including severe infections, mycobacterial disease, autoimmune conditions, hypersensitivity disorders, and genetic conditions. The pathophysiology of disease is understood in terms of interdependent concepts of chronic infection, inflammation, impaired mucociliary clearance, and structural lung damage. Neutrophilic inflamm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 171 publications
(214 reference statements)
0
29
0
1
Order By: Relevance
“…The endotype linked to the type of inflammation is probably the best characterized. Although the majority of bronchiectasis cases present predominantly neutrophilic inflammation [45][46][47] , there is increasing evidence that eosinophilic inflammation can be substantial, and even predominant, in some patients, even in the absence of asthma and underlying diseases associated with a greater degree of eosinophilia. It is also important not to overlook the role played by T cells in the inflammatory picture of bronchiectasis [48][49] .…”
Section: Endotypes In Bronchiectasismentioning
confidence: 99%
See 1 more Smart Citation
“…The endotype linked to the type of inflammation is probably the best characterized. Although the majority of bronchiectasis cases present predominantly neutrophilic inflammation [45][46][47] , there is increasing evidence that eosinophilic inflammation can be substantial, and even predominant, in some patients, even in the absence of asthma and underlying diseases associated with a greater degree of eosinophilia. It is also important not to overlook the role played by T cells in the inflammatory picture of bronchiectasis [48][49] .…”
Section: Endotypes In Bronchiectasismentioning
confidence: 99%
“…Neutrophils play a crucial role in the pathophysiology of most bronchiectasis patients, particularly those with bronchial infection by pathogenic microorganisms. Neutrophils are capable of inducing and producing a large amount of pro-inflammatory molecules with proteolytic and elastolytic characteristics that, along with bacterial products, cause damage in the bronchial wall and the local defence mechanisms [45][46][47] . Of all these molecules, neutrophil elastase is one of the most significant and, moreover, it has proved to be a promising biomarker of inflammatory activity at a bronchial level, as confirmed by several studies that have observed its relationship with the severity of bronchiectasis.…”
Section: Endotype 1 Neutrophilic Inflammationmentioning
confidence: 99%
“…Healthy lungs clear particulate matter and infections via 3 principal mechanisms: the mucociliary elevator, normal breathing cycles, and cough 5 . In disease, increased mucous volume, impaired ciliary function, and poor cough combine to disrupt the normal mobilization of secretions, leading to increased risk of infection and engendering a vicious cycle of recurrent infections, inflammation, and damage to the airways 6 …”
Section: Predisposing Pathophysiologiesmentioning
confidence: 99%
“…With a prominent presence in a number of airways diseases including cystic fibrosis [ 16 ], COPD [ 17 ], bronchiectasis and asthma [ 18 , 19 ], neutrophils are now recognised as central players in the development of persistent chronic inflammation. Studies exploring neutrophil function have reported dysregulated neutrophil chemotaxis in cystic fibrosis [ 16 ], COPD [ 20 ] and in AATD [ 4 ], with increased neutrophil extracellular traps in sputum samples from individuals with bronchiectasis correlating with worse clinical outcomes [ 21 ].…”
Section: Introductionmentioning
confidence: 99%